Staff experiences of closing out a clinical trial involving withdrawal of treatment: qualitative study - Lawton, J; White, D; Rankin, D; Elliott, J; Taylor, C; Cooper, C; Heller, S; Hallowell, N (BioMed Central, 2017)
BACKGROUND: The ending of a clinical trial may be challenging, particularly if staff are required to withdraw the investigated treatment(s); however, this aspect of trial work is surprisingly under-researched. To address this gap, we explored the experiences of staff involved in closing out a trial that entailed withdrawal of treatment (insulin pumps) from some patients. METHODS: Interviews were conducted with n = 22 staff, recruited from seven trial sites. Data were analysed thematically. RESULTS: Staff described a myriad of ethical and emotional challenges at closeout, many of which had been unforeseen when the trial began. A key challenge for staff was that, while patients gave their agreement to participate on the understanding that pump treatment could be withdrawn, they often found themselves benefitting from this regimen in ways they could not have foreseen. Hence, as the trial progressed, patients became increasingly anxious about withdrawal of treatment. This situation forced staff to consider whether the consent patients had given at the outset remained valid; it also presented them with a dilemma at closeout because many of those who had wanted to remain on a pump did not meet the clinical criteria required for post-trial funding. When deciding whether to withdraw treatment, staff not only had to take funding pressures and patient distress into account, but they also found themselves caught between an ethic of Hippocratic individualism and one of utilitarianism. These conflicting pressures and ethical considerations resulted in staff decision-making varying across the sites, an issue that some described as a further source of ethical unease. Staff concluded that, had there been more advanced planning and discussion, and greater accountability to an ethics committee, some of the challenges they had confronted at closeout could have been lessened or even prevented. CONCLUSIONS: The same kinds of ethical issues that may vex staff at the beginning of a trial (e.g. patients having unrealistic expectations of trial participation; staff experiencing conflicts between research and clinical roles) may re-present themselves at the end. To safeguard the wellbeing of staff and patients, greater planning, coordination and ethical oversight should go into the closeout of trials involving withdrawal of treatment(s). TRIAL REGISTRATION: International Standard Randomised Controlled Trials Number (ISRCTN) Registry, ISRCTN61215213 . Registered on 11 May 2011.